2014
DOI: 10.1186/s40168-014-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial shifts in the aging mouse gut

Abstract: BackgroundThe changes that occur in the microbiome of aging individuals are unclear, especially in light of the imperfect correlation of frailty with age. Studies in older human subjects have reported subtle effects, but these results may be confounded by other variables that often change with age such as diet and place of residence. To test these associations in a more controlled model system, we examined the relationship between age, frailty, and the gut microbiome of female C57BL/6 J mice.ResultsThe frailty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
318
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(382 citation statements)
references
References 74 publications
54
318
10
Order By: Relevance
“…5A and Fig. S8 B and C) (45,46). At T2 (21 mo of age), the microbiome of HGxoLG mice was distinct from that of HG mice and started to resemble LG microbiomes (Fig.…”
Section: −5mentioning
confidence: 94%
“…5A and Fig. S8 B and C) (45,46). At T2 (21 mo of age), the microbiome of HGxoLG mice was distinct from that of HG mice and started to resemble LG microbiomes (Fig.…”
Section: −5mentioning
confidence: 94%
“…Importantly, the mucin-degrading bacterium Akkermansia muciniphila was shown to reverse these metabolic disorders by strengthening the intestinal barrier [589]. In our study old conventional mice had lower abundance of Akkermansia, which has also been reported previously both in humans and mice [590,591]. Akkermansia was also less abundant after transfer of old microbiota to germ-free mice at early time points.…”
Section: Discussionsupporting
confidence: 87%
“…Mouse models have been used to address several gut microbiota-associated diseased states, such as obesity [7] and inflammation-associated diseases [8]. Furthermore, mouse models have been used to examine the correlation between gut microbiota and aging [9], as well as the role of the gut microbiota in the host’s susceptibility to colonic tumorigenesis [10,11]. Although age, microbiota and tumorigenesis are strongly confounded, no studies have yet related age and CRC to the gut microbiota in mouse models.…”
Section: Introductionmentioning
confidence: 99%